Examining Elementary School Science Achievement Gaps Using an Organizational and Leadership Perspective. (2nd December 2015) - Settlage, John; Butler, Malcolm B.; Wenner, Julianne; Smetana, Lara K.; McCoach, Betsy
Abstract : There is the tendency to explain away successful urban schools as indicative of the heroic efforts by a tireless individual, effectively blaming schools that underperform for a lack of grit and dedication. This study reports the development of a research instrument (School Science Infrastructure, or SSI) and then applying that tool to an investigation of equitable science performance by elementary schools. Our efforts to develop a science‐specific instrument to explore associations between school‐level variables and equitable science performance are informed by James Coleman's tripartite notion of social capital: the "wealth" of organizations is encompassed within their social norms, informational channels, and reciprocating relationships. Grounded in school effectiveness research and social capital theory, the instrument that we report on here is a valid and reliable tool to support meso‐level investigations of factors contributing to school variations in science achievement.